2018
DOI: 10.1007/s10535-017-0757-0
|View full text |Cite
|
Sign up to set email alerts
|

Wheat chromosome instability in the selfed progeny of the double monosomics 1Rv-1A

Abstract: Structural alterations of chromosomes are often found in wheat-rye hybrids. In the majority of cases modifications are observed for rye chromosomes, yet chromosome aberration cases are described for wheat, including the progeny of Triticum aestivum disomic and monosomic addition lines. Since wheat-rye substitution and translocation lines are the source of rye chromatin in wheat breeding programs, information on possible chromosome changes in the genomes of introgressive forms is important. Chromosome behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…If the cohesion is removed early, at the transition of metaphase I to anaphase I, univalents display premature separation of sister chromatids and undergo equational division [ 28 , 33 , 44 ]. Alternatively, if the removal of cohesion is incomplete or the removal continues during anaphase I, the spindle collapses due to opposing forces between the spindle microtubules and the remnant kinetochore cohesion, laggards occur, and an unreduced restitution nucleus is generated [ 28 , 29 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the cohesion is removed early, at the transition of metaphase I to anaphase I, univalents display premature separation of sister chromatids and undergo equational division [ 28 , 33 , 44 ]. Alternatively, if the removal of cohesion is incomplete or the removal continues during anaphase I, the spindle collapses due to opposing forces between the spindle microtubules and the remnant kinetochore cohesion, laggards occur, and an unreduced restitution nucleus is generated [ 28 , 29 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous equational division of univalents and reductional division of bivalents and multivalents on the same spindle, as observed in this and other studies, can thus be understood. As noted earlier, variability in the dissolution of centromeric cohesion in univalents during meiosis I may lead to segregational failure [ 44 , 45 ]. Several studies in the Triticeae and in grasshoppers have shown that the greater the number of univalents, the greater the chance of spindle collapse leading to meiotic restitution and unreduced gametes [ 29 , 34 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Флуоресцентная in situ гибридизация (FISH). Митотические и мейотические препараты для FISH готовили по описанной ранее методике (Silkova et al, 2018). Митотические препараты готовили из корешков вегетирующих растений BC 3 F 1 .…”
Section: материал и методыunclassified
“…Работы по передаче чужеродного генетического материала в геном пшеницы не теряют своей актуальности, формы пшеницы с новыми ценными признаками создаются во многих лабораториях мира, а потенциал генофонда ржи как источник хозяйственно ценных признаков далеко не исчерпан (An et al, 2013;Ren et al, 2017;Schlegel, 2019). В качестве источника важных признаков используются линии с пшенично-ржаным замещением хромосом 2R(2D) 1 и центрическими транслокациями, в структуру которых включено длинное плечо хромосомы ржи 2RL.…”
Section: Introductionunclassified